Editorial Vol.10(1) - Tripathi, Yashodham (A Bi-annual South Asian Journal of Research & Innovation, 2023)
It is our pleasure to present the 10th volume of the journal of scholars to all academic as well as the non academic research article readers in the education sectors. This journal aims to contribute in understanding local socioeconomic and cultural realities, the major objective of this journal is to empower the researchers. Through its publications, the journal give priority to the problems and suggestions on the methodological as well as substantive are in education. This journal encourages the researchers as well as other scholars in the field of education to publish their research findings, which can include dissertation summaries and other educational research monographs. In thus provide an ample opportunities to students to take part in academic exercise to promote knowledge. It is not our ambition to develop a distinct education school in South Asia but we hope to contribute to develop a distinct education of this region by providing supplementary information in our field. We thank to all contributors who supported us in many ways to publish this journal.